Child Sexual Violence Prevention Model in Ketapang Regency, Indonesia - Rupita Rupita; Syarmiati Syarmiati; Nurul Amira Fitriani; Zulkarnain Zulkarnain; Maulidya Indriani (Dealings Foundation Institute, 2026)
This study aims to analyze the model of prevention of sexual violence against children by the Women and Children's Empowerment Division at the Social Services Office of Ketapang Regency, West Kalimantan Province. This study uses a qualitative descriptive method. Data will be collected from research subjects using a purposive sampling method, meaning that the subjects are drawn from individuals directly involved in and familiar with the issues surrounding the prevention of sexual violence against children in Ketapang Regency. Data will be analyzed using techniques. The results indicate that the model for preventing sexual violence against children in Ketapang Regency has been implemented through various strategies, ranging from appropriate sexual education, campaigns and raising public awareness, to inter-agency collaboration and psychological support for victims. The Women and Children's Empowerment Division at the Social Services Office has implemented promotive, preventive, and curative efforts such as outreach, establishing a child protection network, providing reporting mechanisms, and providing support services. However, the high number of cases indicates that these measures have not been fully effective due to weak community participation, minimal synergy between parties, limited specific prevention programs, and obstacles in law enforcement.